Queensland Interstate Migration Determinants and Dynamics - Fitzpatrick, R. A. (My University, 2013)
For more than three decades Queensland has consistently recorded the highest net interstate migration (NIM) gains of any State or Territory in Australia. Since 2002, however, NIM to Queensland has fallen to lows not observed since the 1970s as a result of declining gross inflows. This thesis examines both Queensland's primacy and decline as an interstate migration destination and identifies a number of the processes at work. These include the reduction in house price differentials between Queensland and the two other large mainland states, New South Wales and Victoria, in a wider context of declining national mobility rates, an ageing population and a maturation of the Australia space economy. Census data are employed in a shift-share analysis of Australian interstate migration flows to identify the extent to which changes in population age structure have impacted migration probabilities over the last decade. Secondly, quarterly interstate migration flows from 1996(3) to 2012(2) are modelled to identify determinants of migration to Queensland and if they have changed over time. A logistic model of system-wide migration similar to Sasser (2010) was estimated first, to identify determinants important within the national migration system. Quarterly interstate migration was subsequently modelled on a bilateral basis with respect to Queensland in an unobserved components framework. This analysis was extended by a comparison of flows disaggregated by age to identify how the relative importance of migration determinants varies over the life course. The determinants identified were then compared to those identified as important in the national system.
Keywords: Housing -- Moving; Location -- QLD; Housing, communities and neighbourhoods; Location; Housing; QLD; Moving; Housing, community and neighbourhoods